Effect of Corrosive Liquid Lead Coolant on the Structural Stability of Iron Material - Sudarmadi, Sudarmadi; Sutisna, Sutisna; Cahyono, Bowo Eko; Widiasih, Widiasih (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
For the design of fast nuclear reactors, usually it use the lead metal alloys for coolant materials. Researches about lead coolants, has been carried out experimentally. However, experimental studies in the nuclear material field, besides being expensive, usually also require high safety. In particular, research on the corrosive properties of liquid lead for structural materials requires serious treatment if carried out experimentally. In this case, the computational method is very helpful to overcome these obstacles. In our research we use the molecular dynamics simulation method to know the effect of temperatures and effect of liquid lead corrosion attack to iron material. We want to know that which one is most crucial that causing the damage of the materials: it is due to temperature or due to liquid lead attack. It has been observed from MSD curves of simulation results that the liquid lead can make iron material experiencing most damage if compared with temperature effect The interactions among atoms are described by the Lennard-Jonnes interaction potential. The simulations was run and supported using Moldy and Ovito software.Keywords: Corrosion of molten lead, fast nuclear reactor, molecular dynamics simulation, Moldy, MSD, Ovito.